Imaging spectrum of amyloid-related imaging abnormalities associated with aducanumab immunotherapy - Sotoudeh, Houman; Alizadeh, Mohammadreza; Shahidi, Ramin; Shobeiri, Parnian; Saadatpour, Zahra; Wheeler, C. Austin; Natelson Love, Marissa; Tanwar, Manoj (Frontiers in Radiology, 2024)
Alzheimer's Disease (AD) is a leading cause of morbidity. Management of AD has traditionally been aimed at symptom relief rather than disease modification. Recently, AD research has begun to shift focus towards disease-modifying therapies that can alter the progression of AD. In this context, a class of immunotherapy agents known as monoclonal antibodies target diverse cerebral amyloid-beta (Aβ) epitopes to inhibit disease progression. Aducanumab was authorized by the US Food and Drug Administration (FDA) to treat AD on June 7, 2021. Aducanumab has shown promising clinical and biomarker efficacy but is associated with amyloid-related imaging abnormalities (ARIA). Neuroradiologists play a critical role in diagnosing ARIA, necessitating familiarity with this condition. This pictorial review will appraise the radiologic presentation of ARIA in patients on aducanumab.